2016
DOI: 10.1002/mus.25025
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of muscle membrane properties in myotonic dystrophy

Abstract: Introduction Myotonia in myotonic dystrophy types 1 (DM1) and 2 (DM2) is generally attributed to reduced chloride channel conductance. We used muscle velocity recovery cycles (MVRCs) to investigate muscle membrane properties in DM1 and DM2, with comparisons with myotonia congenita (MC). Methods MVRCs and responses to repetitive stimulation were compared between patients with DM1 (n=18), DM2 (n=5), MC (n=18), and normal controls (n=20). Results Both DM1 and DM2 showed enhanced late supernormality after mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 44 publications
1
23
2
Order By: Relevance
“…The recording technique was performed as described previously for tibialis anterior (TA) and is briefly summarized below. For details of the MVRC and ramp protocols see Tan et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recording technique was performed as described previously for tibialis anterior (TA) and is briefly summarized below. For details of the MVRC and ramp protocols see Tan et al .…”
Section: Methodsmentioning
confidence: 99%
“…MVRCs, consisting of MRRP, ESN and LSN, can be reliably measured in human muscles by direct stimulation and recording of a bundle of adjacent muscle fibers with a sequence of paired electrical pulses of equal amplitude and varying interstimulus interval (ISI) . They indicate a rapid onset of membrane depolarization during limb ischemia and have been used to infer muscle membrane depolarization in renal failure and to provide information about membrane abnormalities in critical illness myopathy, Andersen‐Tawil syndrome, myotonia congenital (MC), and myotonic dystrophy …”
mentioning
confidence: 99%
“…However, Tan et al . recently concluded that Na + /K + pump dysfunction is also implicated in DM1 (but not in DM2) from insights gained in muscle excitability using a recently developed in vivo technique, multifiber muscle velocity recovery cycle (MVRC) assessment of a cohort of patients with DM1.…”
mentioning
confidence: 99%
“…We also expected that such dysfunction would be likely to manifest as evidence of depolarization of the resting muscle membrane potential (RMMP) in more severely affected individuals due to loss of its electrogenic function. The current study tested for this by using MVRCs, a technique already used to study a number of acquired and inherited conditions of skeletal muscle …”
mentioning
confidence: 99%
“…Muscle velocity recovery cycle (MVRCs) assessment represents a new automated technique whereby muscle membrane polarisation properties can be quantitated in vivo. The study aim was to characterise the excitability attributes of DM1 and DM2 comparing with that of normal control subjects and the results of a recently published myotonic dystrophy cohort using the same technique 1 .…”
mentioning
confidence: 99%